Production of moth sex pheromones for pest control by yeast fermentation - Holkenbrink, Carina; Ding, Bao Jian; Wang, Hong Lei; Dam, Marie Inger; Petkevicius, Karolis; Kildegaard, Kanchana Rueksomtawin; Wenning, Leonie; Sinkwitz, Christina; Lorántfy, Bettina; Koutsoumpeli, Eleni; França, Lucas; Pires, Marina; et al. (Metabolic Engineering, 2020)
The use of insect sex pheromones is an alternative technology for pest control in agriculture and forestry, which, in contrast to insecticides, does not have adverse effects on human health or environment and is efficient also against insecticide-resistant insect populations. Due to the high cost of chemically synthesized pheromones, mating disruption applications are currently primarily targeting higher value crops, such as fruits. Here we demonstrate a biotechnological method for the production of (Z)-hexadec-11-en-1-ol and (Z)-tetradec-9-en-1-ol, using engineered yeast cell factories. These unsaturated fatty alcohols are pheromone components or the immediate precursors of pheromone components of several economically important moth pests. Biosynthetic pathways towards several pheromones or their precursors were reconstructed in the oleaginous yeast Yarrowia lipolytica, which was further metabolically engineered for improved pheromone biosynthesis by decreasing fatty alcohol degradation and downregulating storage lipid accumulation. The sex pheromone of the cotton bollworm Helicoverpa armigera was produced by oxidation of fermented fatty alcohols into corresponding aldehydes. The resulting yeast-derived pheromone was just as efficient and specific for trapping of H. armigera male moths in cotton fields in Greece as a conventionally produced synthetic pheromone mixture. We further demonstrated the production of (Z)-tetradec-9-en-1-yl acetate, the main pheromone component of the fall armyworm Spodoptera frugiperda. Taken together our work describes a biotech platform for the production of commercially relevant titres of moth pheromones for pest control via yeast fermentation.
Keywords: Fatty acyl-CoA desaturase; Fatty alcohols; Lepidoptera; Yarrowia lipolytica